Single and multiple excitations in double-core-hole states of free water molecules. (22nd October 2020) - Marchenko, T; Carniato, S; Goldsztejn, G; Travnikova, O; Journel, L; Guillemin, R; Ismail, I; Koulentianos, D; Martins, J; Céolin, D; Püttner, R; Piancastelli, M N; et al.
Abstract: We present a combined experimental and theoretical study of the double-core-hole photoelectron spectrum obtained in isolated water molecules irradiated with hard x-rays above the oxygen K −2 threshold. States of the type O K −2 V and multiply excited states are created by single-photon absorption and subsequent one-electron emission. A detailed analysis enabled by high experimental resolution reveals dissociative nuclear dynamics in the K −2 V pre-edge states. At the binding energies above the K −2 double-ionization potential, a complex spectral pattern is observed and attributed to highly excited states involving multiple shake-up excitation processes with the aid of state-of-the-art theoretical calculations. A strong broadening due to the nuclear motion indicates a highly dissociative nature of these multiply excited states, in agreement with the theoretical analysis.